Abdurrahman Wahid Structural Da'wah Activities - Awaludin Pimay; Agus Riyadi (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2021)
This study aims to see how Gus Dur's da'wah activities with the position of President and what da'wah policies he made. This qualitative research uses historical methods and documentation as the primary data sources. The results showed that Gus Dur, who served as President from 20 October 1999 to 23 July 2001, was based on a study of policies in the form of laws and regulations he signed, some of which included da'wah policies. These da'wah policies are related to Muslim worship (Keppres 8/2001, Presidential Decree 97/2000, Presidential Decree 22/2001), human rights (UU 1/2000, Presidential Decree 12/2001, Presidential Instruction 9/2000, Presidential Decree 1/2000, Presidential Decree No. 6/2000, Presidential Decree 69/2000), separatism (Presidential Decree 27/2000, Presidential Decree 75/2000, Presidential Decree 28/2000, Presidential Decree 47/2000), and corruption (PP 19/2000, PP 71/2000). Gus Dur used his power to preach democracy and humanity as the direction of his struggle.